Capitalismo dependente e a subordinação das políticas públicas educacionais para o ensino superior nos governos FHC e Lula (1995-2010): contribuição crítica com base na teoria marxista da dependência - Corrêa, Marcos Britto (2021)
The discourse upon the Higher Education system expansion in Brazil was increased as of 2000. Policies like Programa Universidade para Todos (PROUNI) or Programa de Apoio a Planos de Reestruturação e Expansão das Universidades Federais (REUNI) supported this discourse. At the same period, the division regarding the governments ran by Fernando Henrique Cardoso (FHC) (1995-2002) and Luiz Inácio Lula da Silva (2003-2010) was also recurrent. These governments were deemed opposed as to the public policies in education for the Higher Educational System. This thesis, which was developed during the Programa de Pós-Graduação em Educação of Universidade Federal de Santa Maria (UFSM) and Kairós – Grupo de Estudos e Pesquisas sobre Trabalho, Políticas Públicas e Educação, introduces a study on the public policies in education for the Higher Education System that were produced from 1995 to 2010. In order to develop the proposed investigation, the Marxist Dependency Theory was adopted. We aimed at approaching not only the State in the dependent capitalism singularity, but also the bibliographic research and analysis of public policies in education. Based on the critical approach path regarding the subordinate and sub-sovereign functioning that satisfies the State with dependent economic formation, the analyzed data showed no ruptures between different governments in the country’s presidency, but supported continuities through the need of reproducing capital with emphasis on financial capital. Due to the fact that they are considered parties of the extended capital reproduction, public policies in education for the Higher Education System produced between 1995 and 2010 reinforced the Brazilian’s underdevelopment development, because they did not change the main forms of value transfer between the country and capitalists of central economies – such policies are limited to the Union budget, which is directed to the Debt System, and to the formation of a workforce mass reserve that underwent overexploitation, having scientific and technological dependency as a foundation. In brief, this study has showed the structural limitation prevailing among public policies in education and its capital reproduction functioning, regardless of the Government in charge of the Republic Presidency. Therefore, when such policies do not point out an effective rupture with economic dependency, at the end, they are subordinate to the reproduction of this dependency. Thus, despite the apparent difference between FHC and Lula’s Governments, the research results showed continuous management of policies that reinforce the Brazilian dependent underdevelopment by following the financial capital demands related to the supposed expansion of the Higher Education System. Such expansion process proved to be, therefore, fallacious when it covered up the real Brazilian underdevelopment as a necessary element to the extended reproduction of capital.